2012
DOI: 10.1002/jcb.23438
|View full text |Cite
|
Sign up to set email alerts
|

Microarray‐based identification of aminopeptidase N target genes in keratinocyte conditioned medium‐stimulated dermal fibroblasts

Abstract: Of the many processes that affect the outcome of wound repair, epidermal-dermal interactions are essential to extracellular matrix (ECM) remodeling and in particular, soluble factors released by keratinocytes are known to have a direct impact on the production of ECM by dermal fibroblasts. Aminopeptidase N (APN) has recently been proposed as a cell-surface receptor for stratifin and is responsible for the stratifin-mediated matrix metalloproteinase-1 (MMP-1) upregulation in fibroblasts. The present study exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…46 Tmprss11d and Tmprss13 encode proteases. 47 49 Anpep is also called CD13 , encoding a membrane protein that plays a role in digesting peptides and may also play roles in regulating keratinocyte-mediated ECM remodeling and fibroblast contractile activity 50 as well as immune responses. 51 Fxyd4 encodes a regulator of the Na, K-ATPase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Tmprss11d and Tmprss13 encode proteases. 47 49 Anpep is also called CD13 , encoding a membrane protein that plays a role in digesting peptides and may also play roles in regulating keratinocyte-mediated ECM remodeling and fibroblast contractile activity 50 as well as immune responses. 51 Fxyd4 encodes a regulator of the Na, K-ATPase.…”
Section: Resultsmentioning
confidence: 99%
“…46 Tmprss11d and Tmprss13 encode proteases. [47][48][49] Anpep is also called CD13, encoding a membrane protein that plays a role in digesting peptides and may also play roles in regulating keratinocyte-mediated ECM remodeling and fibroblast contractile activity 50 as well as immune responses. 51 Fxyd4 Abbreviations: D3.5, gestation day 3.5, preimplantation; D4.5, gestation day 4.5, postimplantation; E2, 17b-estradiol; P4, progesterone; IS, implantation site; inter-IS, interimplantation site; LE, luminal epithelium; GE, glandular epithelium.…”
Section: Gene Expression Confirmation By Real-time Pcr and In Situ Hymentioning
confidence: 99%
“…It is also possible that the activated fibroblasts in turn modulate keratinocyte responses. Moreover, it was recently reported that keratinocytes can induce proteolytic activation of fibroblasts in an aminopeptidase N ‐dependent manner (Lai et al ., ). The dramatic change in rhCol‐III kinetics induced by cell type in vivo demonstrates that care should be taken to identify the cell populations before mixing them in the carrier gel.…”
Section: Resultsmentioning
confidence: 97%
“…Cells were seeded on a 96-well plate and transfected with siRNA targeting the sequence of CCGAAATGCCACACTGGTCAA of the human ANPEP (CD13) sequence (NM_001150) ( Lai et al, 2012 ). Non-specific scrambled siRNA duplex was also purchased from GenePharma (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%